KAJIAN DURABILITAS DAN PENUAAN ASPHALT CONCRETE-WEARING COURSE (AC-WC) ASBUTON PRACAMPUR TERHADAP VARIASI LAMA RENDAMAN - Attamimi, Mohamad Faldi; Achmad, Fadly; Desei, Frice L. (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Negeri Gorontalo, 2021)
The fundamental problem in roads construction is the road damage that occurs before the road’s designted time is reached. Causes of such a damage consist of weather, water, temperature, or the reduction in the quality of pavement layers due the aging process. The manufacture of test object for Short-Term Oven Aging (STOA) was carried out by heating the test object in loose condition with 135°C of temperature for 4 hours before compaction, while the manufacture of test piece for Long-Term Oven Aging (LTOA) was carried out by heating the test object for 2 days in 85°C temperature after the specimen was compacted. The durability parameters of the AC-WC mixture was observed from Residual Streght Index (RSI), First Durability Index (FDI), and Second Durability Index (SDI). Based on the findings of Pre-Blended Buton Asphalt AC-WC mixture produced 6,0% of Optimum Bitumen Content (OBC). The RSI of the test object in normal, STOA, and LTOA obtained 97,11%, 94,82%, and 95,77% respectively. Furthermore, the FDI of the test object in normal, STOA, and LTOA obtained r value of 0,42%, 0,74%, and 0,60% respectively. Meanwhile, the SDI of the test in normal, STOA, and LTOA obtained a value of 4,87%, 9,75%, and 7,73% respectively. In addition, the Sa of the test object in normal, STOA, and LTOA in 96 hours of soaking were 95,13%, 90,25%, and 92,27% respectively. All in all, the finding showed that the AC-WC mixture with Pre-Blended Buton Asphalt in normal condition attained 72 hours of durability, while for the test specimen which is subjected to aging (STOA and LTOA) attained 48 hours of durability.